Circulating microvesicle number, function and small RNA content vary with age, gender, smoking status, lipid and hormone profiles. Issue 156 (August 2017) - Enjeti, Anoop K.; Ariyarajah, Anita; D'Crus, Angel; Seldon, Michael; Lincz, Lisa F.
Abstract: Background: Characterization of circulating microvesicles (MV) in healthy subjects in relation to various biological factors is not well studied. Objectives: We evaluated the influence of age, gender, smoking status, lipid and hormone profiles on circulating MV in healthy subjects. Methods: Platelet free plasma from 143 volunteer blood donors (males = 80, females = 63) was evaluated by standardized flow cytometry for MV expressing CD41 (platelet-derived), CD105 (endothelial-derived), CD235 (red cell-derived), TF (tissue factor) and phosphatidylserine (PS) MV. Procoagulant function was measured by the Xa based assay (XaCT) and endogenous thrombin potential (ETP) using thrombin generation assay. Results: Those ≤ 29 years and ≥ 60 years had higher levels of MV subsets (CD41, CD235, TF and PS) compared to those aged 30–59 years. The median CD41, CD105, CD235, TF and PS expressing MV by flow cytometry were similar or lower in females, whilst procoagulant activity by the XaCT assay was higher (p = 0.002). In smokers (n = 21), certain MV subsets (CD41, TF and PS) and functional activity (ETP) was lower (p < 0.05). Regression analysis showed that MV parameters of CD41, CD105, TF and ETP could be predicted independently by age, whilst smoking predicted for CD105, CD235, TF, PS and ETP. Certain MV parameters also correlated with BMI, lipid and hormone levels. The small RNA and miRNA levels did not differ by age group, smoking status or gender. Conclusions: It is important to recognize that differences may arise depending on age, gender, BMI, lipid, hormone levels and smoking status in apparently healthy subjects when evaluating MV for pathogenic potential. Highlights: The influence of age, gender, smoking, lipid and hormone profiles on circulating MV in 143 healthy adults was evaluated. The levels, function and small RNA content of MV was assessed by optical and functional assays. Those ≤ 29 years and ≥ 60 years had higher levels of MV by flow cytometry when compared to those between 30–59 years of age. MV level and function were also influenced by gender, smoking status, lipid and hormone profile.